Exploring Challenges of Dalit School Education in Nepal An Ethnographic Study (KMC Journal, 2022)
The presence of the Dalits in the mainstream education needs social, historical, legal, cultural, political, and spiritual interferences to emancipate the Dalits from the chain of ignorance. This study, therefore, aimed to explore the challenges for the Dalits in approaching school education in the context of Nepal. Here, after identifying the Dalit concern, I reviewed the related literature. Similarly, the inquiry strategy was qualitative and ontologically based on multiple realities. Thus, I used an ethnographic research design with unstructured interview sessions and participatory observation. Likewise, school teachers, head-teacher, Dalit students, parents, School Management Committee members, and community people were purposively selected to collect information. The data was analyzed and interpreted with the lens of cultural difference theory and caste hierarchy theory to generate meanings. I also used my reflexivity to be aligned with the research and experiences obtained in the study field. The conclusion thus emphasized that the Dalits in Nepal are excluded in terms of cultural differences concerning the non-Dalits and caste hierarchy that is severely rooted in the socio-cultural context of Nepal.